Does the transformation of accounting firms' organizational form improve audit quality? Evidence from China - Chunfei Wang; Huan Dou (China Journal of Accounting Research, 2015)
In this study, we examine the effects of the transformation of accounting firms' organizational form on audit quality. We find that the transformation from limited liability to limited liability partnerships has a significant negative effect on the absolute value of discretionary accruals of audited companies. In particular, the transformation has a significant negative effect on positive discretionary accruals and no effect on negative discretionary accruals. We also find that CPAs are more likely to issue modified audit opinions in the year after the transformation, and that there is no evidence that accounting firm size and listed company ownership influence the relationship between the transformation and audit quality. Our conclusions provide empirical evidence for policy makers and enrich the literature on accounting firms' organizational forms.
Keywords: 650; Organizational forms of accounting firms; Limited liability partnership; Audit quality